The role of agriculture in saving the rain forest - Vosti, Stephen A. (International Food Policy Research Institute, 1995)
Tropical forests are disappearing rapidly--with potentially high social costs in biodiversity loss and carbon emissions. While agriculture is critical to the long-term solution of sustainable livelihood and food security in the humid tropics, it is only part of the story. To take pressure off land, nonagricultural sectors of rural economies must be strengthened in addition to improving agricultural productivity. In short, what is called for is a portfolio of agricultural, extractive, and nonagricultural activities that involve technological innovation designed for higher productivity of land and labor. These activities must translate into higher profitability for the farmer at lower cost to the environment and must be compatible with the constrained resource position of the small farmer.